ACOUSTIC WAVES – SONAR EQUATION: ACOUSTIC WAVES – SONAR EQUATION - Stoykov, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The earliest methods used to directly measure water depth were the guide line (lead line) and drilling. Their simple principles of operation ensure their continued use for many centuries.